The Impact of Management Information Systems on Decision-Making Efficiency - Aminuddin Hamdat; Ceskakusumadewi B; Abdul Gafar Samalam; Muhammad Rizal; Izaac L.D Lawalata (Yayasan Vifada Cendikia Indonesia, 2024)
This study investigates the impact of Management Information Systems (MIS) on organizational decision-making efficiency. It aims to explore how MIS enhances decision-making processes by providing real-time data and comprehensive analytics, aligning with organizational goals, and leveraging advanced technologies like AI and cloud computing. The research employs a mixed-method approach, combining qualitative and quantitative data. Surveys were conducted among senior managers and IT professionals across various sectors to gather insights into MIS's practical applications and challenges. Additionally, a review of theoretical frameworks, such as the Technology Acceptance Model (TAM) and the Resource-Based View (RBV), was undertaken to contextualize the empirical findings. The findings reveal that MIS significantly enhances decision-making efficiency by providing timely and relevant information. Real-time data capabilities and advanced analytics enable managers to make informed decisions quickly, improving organizational agility and responsiveness. Empirical evidence suggests that organizations with integrated and strategically aligned MIS report higher decision accuracy and speed. However, the effectiveness of MIS is contingent on contextual factors like organizational culture and user proficiency. Integrating AI-driven analytics and cloud computing further amplifies MIS capabilities, though continuous technological updates are necessary to maintain system relevance and effectiveness. The study underscores the critical role of MIS in modern business environments, emphasizing the need for strategic alignment and integration with organizational goals. Organizations should invest in advanced MIS technologies, comprehensive training programs, and robust data governance practices for optimal outcomes. These investments are crucial for leveraging MIS to enhance decision-making efficiency, fostering more agile and competitive organizations.